Snowflake Bentley - Martin, Jacqueline Briggs; Azarian, Mary (Boston : Houghton Mifflin, 1998)
A biography of a self-taught scientist who photographed thousands of individual snowflakes in order to study their unique formations.
Keywords: Bentley, W. A. -- 1865-1931 -- Juvenile literature; Bentley, W. A. -- 1865-1931.; Snowflakes -- Juvenile literature; Nature photography -- Juvenile literature; Meteorologists -- United States -- Biography -- Juvenile literature; Photographers -- United States -- Biography -- Juvenile literature; Scientists; Snow